2015
DOI: 10.1371/journal.pone.0143089
|View full text |Cite
|
Sign up to set email alerts
|

Technical Approach Determines Inflammatory Response after Surgical and Transcatheter Aortic Valve Replacement

Abstract: ObjectiveTo investigate the periprocedural inflammatory response in patients with isolated aortic valve stenosis undergoing surgical aortic valve replacement (SAVR) or transcatheter aortic valve implantation (TAVI) with different technical approaches.Material and MethodsPatients were prospectively allocated to one of the following treatments: SAVR using conventional extracorporeal circulation (CECC, n = 47) or minimized extracorporeal circulation (MECC, n = 15), or TAVI using either transapical (TA, n = 15) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
3
10
1
Order By: Relevance
“…Elevated levels of IL-6 as part of the systemic inflammatory response syndrome have shown to predict outcome and mortality (3,27). In this study, IL-6 levels did not return to baseline and reached the highest level at 24 h in the MiECC group, which may indicate that post-procedural IL-6 release continues beyond 48 h as already demonstrated in another trial by our group while using a type II MiECC setup (28). There are conflicting results regarding this cytokine response in CPB (6).…”
Section: Discussioncontrasting
confidence: 46%
“…Elevated levels of IL-6 as part of the systemic inflammatory response syndrome have shown to predict outcome and mortality (3,27). In this study, IL-6 levels did not return to baseline and reached the highest level at 24 h in the MiECC group, which may indicate that post-procedural IL-6 release continues beyond 48 h as already demonstrated in another trial by our group while using a type II MiECC setup (28). There are conflicting results regarding this cytokine response in CPB (6).…”
Section: Discussioncontrasting
confidence: 46%
“…However, in addition to the amount of inflammation, a persistent elevated inflammatory marker seems to have a negative association with outcomes including mortality (17). In agreement with earlier reports, we also observed a peak level of CRP after TAVI on the third postoperative day (14,28). In comparison to CRP and PCT, IL-6 showed a significant difference on the immediate postoperative course with significant higher values in the SAVR-group.…”
Section: Discussionsupporting
confidence: 92%
“…The main explanation of this finding is the presence or absence of cardiopulmonary bypass activating the inflammatory pathway (26), which is a known fact that cardiac surgery with cardiopulmonary bypass activates a systemic inflammatory response that is associated with adverse outcomes (27). These results are similar to the results of Erdoes et al who reported a significant activation of various inflammatory pathways in invasive procedures (e.g., SAVR) in comparison to less invasive procedures (e.g., TAVI) (14). However, in addition to the amount of inflammation, a persistent elevated inflammatory marker seems to have a negative association with outcomes including mortality (17).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, even after the surgical procedure, the inflammatory state persists in almost half of the patients [ 7 ]. However, recently, it has been proposed that the technical approach determines the inflammatory response after surgical and transcatheter aortic valve replacement [ 8 ].…”
Section: Introductionmentioning
confidence: 99%